The Role of Employee Engagement in Linking Supportive Workplace Environment and Digital-Era Enablers to Employee Performance: Evidence from Indonesia - Endang Sukandar; Erna Waty; Felicia Pandria; Gusti Ria Juita; Nelson Lianto (Eduvest - Journal of Universal Studies, 2026)
In the era of digital transformation, organizations face increasing challenges in aligning Supportive Workplace Environment practices with various Digital-Era Enablers in order to sustain and enhance Employee Engagement and Employee Performance. This study aims to empirically examine the effects of Supportive Workplace Environment—comprising Work Recognition, Work Motivation, and Career Development—and Digital-Era Enablers—including Knowledge Sharing, Employee Mobility, Training & Development, and Psychological Empowerment—on Employee Engagement, as well as the subsequent effect of Employee Engagement on Employee Performance. This study employs a quantitative approach using a cross-sectional survey design involving 317 permanent employees across various industries in Indonesia. The research instrument was developed by integrating questionnaire items derived from two primary reference journals. Data were analyzed using multiple linear regression and simple linear regression with the assistance of SPSS software. The results indicate that Psychological Empowerment, Training & Development, Work Recognition, and Knowledge Sharing have positive and statistically significant effects on Employee Engagement. In contrast, Work Motivation, Career Development, and Employee Mobility do not exhibit statistically significant effects. Furthermore, Employee Engagement is found to have a positive and statistically significant effect on Employee Performance. These findings suggest that in an increasingly digitalized work environment, employee engagement is more strongly influenced by factors that enhance psychological autonomy, capability development, and knowledge exchange mechanisms than by traditional motivational practices. This study contributes to the literature by integrating Supportive Workplace Environment and Digital-Era Enablers into a single empirical framework.